J Phys Med Rehabil 2022
DOI: 10.33696/rehabilitation.4.029
|View full text |Cite
|
Sign up to set email alerts
|

Manual Therapy Improves Immediate Blood Flow and Tissue Fiber Alignment of the Forearm Extensors

Abstract: Background: Manual therapy is commonly used by clinicians to improve blood flow and tissue fiber orientation. Hypothesis/Purpose: Using diagnostic ultrasound, the purpose of the study was to examine how the application of Positional Release Therapy (PRT), instrumented assisted soft tissue mobilization (IASTM), therapeutic ultrasound (US) and a combination of all three, affect lateral elbow immediate blood flow and tissue fiber alignment. Study Design: Controlled laboratory study. Methods: Twenty-five participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Thus, IASTM researchers have investigated the effectiveness of light pressure to optimize treatments. Preliminary evidence that IASTM works from a neurophysiological mechanism is supported by findings of modulated grip strength [7] improved tactile discrimination [11] and increased blood flow [26] following light pressure IASTM. While each of these studies demonstrated that lighter forces can be effective, there is also evidence that increased forces stimulate connective tissue remodeling, reduce fascial adhesions, and break down scar tissue that limit ROM [4,27,28].…”
Section: Discussionmentioning
confidence: 94%
“…Thus, IASTM researchers have investigated the effectiveness of light pressure to optimize treatments. Preliminary evidence that IASTM works from a neurophysiological mechanism is supported by findings of modulated grip strength [7] improved tactile discrimination [11] and increased blood flow [26] following light pressure IASTM. While each of these studies demonstrated that lighter forces can be effective, there is also evidence that increased forces stimulate connective tissue remodeling, reduce fascial adhesions, and break down scar tissue that limit ROM [4,27,28].…”
Section: Discussionmentioning
confidence: 94%